2022
DOI: 10.1007/s12144-022-03384-5
|View full text |Cite
|
Sign up to set email alerts
|

Multigroup analysis of the relationship loneliness, fear of missing out, problematic internet usage and peer perception in gifted and normally developing adolescents

Abstract: The current study examined the effects of Internet usage characteristics and peer perception on loneliness. The mediating role of Internet usage characteristics was examined in the relationship between loneliness and peer perception. The sample included 661 Turkish adolescents (N girls =379, 57.34%; N gifted = 211, 31.92%) aged 11–18 years. Structural equation model analyzes were conducted to test the hypothesis model across the group. Moreover, multigroup structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Furthermore, by definition, a key component of FoMO is a relatively high level of negative affect. Several studies have shown that FoMO is associated with other negative feelings, such as envy (Yin et al, 2021), loneliness (Tatli & Ergin, 2022), and boredom (Liang et al, 2022), which in turn can lead to lower life satisfaction (Marttila et al, 2021;Mujcic & Oswald, 2018;Spruyt et al, 2016). Cross-sectional studies also found that FoMO was negatively associated with life satisfaction (Blachnio & Przepiorka, 2018;Deniz, 2021;Przybylski et al, 2013).…”
Section: The Mediating Role Of Fomomentioning
confidence: 99%
“…Furthermore, by definition, a key component of FoMO is a relatively high level of negative affect. Several studies have shown that FoMO is associated with other negative feelings, such as envy (Yin et al, 2021), loneliness (Tatli & Ergin, 2022), and boredom (Liang et al, 2022), which in turn can lead to lower life satisfaction (Marttila et al, 2021;Mujcic & Oswald, 2018;Spruyt et al, 2016). Cross-sectional studies also found that FoMO was negatively associated with life satisfaction (Blachnio & Przepiorka, 2018;Deniz, 2021;Przybylski et al, 2013).…”
Section: The Mediating Role Of Fomomentioning
confidence: 99%
“…Based on a survey conducted by the Healthy Minds Network for Research on Adolescent and Young Adult Mental Health and the American College Health Association on 18,764 Gen Zs, depression increased during the Covid-19 pandemic by 40.9% (Al-Saggaf & O'Donnell, 2019). Other symptoms of psychological distress include feelings of loneliness, helplessness, anger, fear, insomnia, avoiding stress, nightmares, dizziness, and palpitations (Hayran & Anik, 2021;Rifaya, 2022;Tatlı & Ergin, 2022). The causes of such symptoms are triggered by stressors in the form of uncertainty, loss of control, helplessness, negative perception (Trikusuma & Hendriani, 2021).…”
Section: Discipling With Storgementioning
confidence: 99%